Hill rice (Oryza sativa l.): Exploring the Malaysian knowledge, perception and intention to purchase - Maikol, Nathaniel; Kamarudin, Shafinah; Sentian, Justin; Mohamad Saad, Mohamad Zaki; Ramlan, Nur Hafizatun; Leong, Wan Teng; Ramaiya, Shiamala Devi (Human Resource Management Academic Research Society, 2023)
Rice has a pivotal role as a crucial staple food for more than 50% of the worldwide population, including the nation of Malaysia. The challenges such as invasive and native pests, water scarcity issues, difficulties in accessing markets, pesticide-related health issues, and farmers' outmigration to find employment affect the production of rice. These challenges, in turn, have indirect implications for achieving self-sufficiency in food security. Hill rice is commonly cultivated by small farmers in Malaysia. Research related to hill rice is still continuous, mainly to investigate the potential value of hill rice to commercialize in order to support rice self-sufficiency in Malaysia. This study aims to explore the Malaysian knowledge regarding hill rice, and to investigate the Malaysian' perception and intention to purchase hill rice. In 2022, a survey was carried out by utilizing the Whatsapp platform as the method of distributing the questionnaire, which was then self-administered by the 133 respondents. The findings indicate that a significant proportion of participants hold a positive view of hill rice, with over 50% expressing an intention to purchase this type of rice. Hence, the results indicate that hill rice had the potential for commercialization. The relevant authorities may consider proposing and implementing an appropriate initiative or project aimed at encouraging smallholders to prioritize the cultivation of hill rice and effectively market this agricultural commodity.